The complete chloroplast genome sequence of Rubus amabilis Focke - Fang Yang; ZongHao Zhang; Li Tong (Mitochondrial DNA. Part B. Resources, 2020)
Rubus is an important genus, as a crucial Chinese traditional and Tibetan medicine, it has big ecological, economic, and social values; however, no plastid genome has been reported to date. Here we report species of this genus complete chloroplast genome of Rubus amabilis Focke. The chloroplast genome of R. amabilis Focke is found to be 155,279 bp in length with 37.31% GC contents. The cp genome sequences contained 131 genes, including 37 tRNA genes, 8 rRNA genes, and 86 mRNA genes, respectively. The complete chloroplast genome of these plants will be benefit for studies on the general characteristics and evolution of the Rubus family genome.